Google Places Enricher: A tool that Makes It Easy to Get and Enrich Google Places API Data - Gubert, Fernanda Regina; Silva, Thiago H. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2022)
The growing number of available APIs means that more developers and interested users need to learn to use unfamiliar interfaces, requiring a learning curve that can compromise productivity. Thus, it becomes important to find ways to facilitate their usability. This work presents a tool that facilitates using the Google Places API, simplifying multiple API calls to cover a region of interest. In addition, the proposed tool also provides features for the enrichment of these data, extending the PoI data from that region with categories from other sources. It is hoped that developers and users without much computer knowledge can benefit from Google Places Enricher, helping to ease the development of new sophisticated urban applications and services.